Joaquim Romero Magalhães and the Early Modern History of Portugal and its Empire: A Tribute - Cunha, Mafalda Soares da (2019)
This document introduces a dossier which is a tribute to Joaquim Romero Magalhães and to the impact of his historical writtings on the historiography of the Portuguese-speaking scholarly world.